Assessment of combined α-GAL enzyme activity and lyso-GL3 for Fabry disease screening in women with chronic kidney disease - Silva, Cassiano Augusto Braga [UNESP]; de Carvalho Barreto, Fellype; Neto, Osvaldo Merege Vieira; Lucca, Leandro Junior; Vieira, Fernando A.; Gueiros, Ana Paula Santana; Boger, Marta V.; Silva, Artur Quintiliano; Guedes, Felipe Leite; Israel, Karla Cristina P.; Gordon, Gina Elizabeth Moreno; Veloso, Valeria S.P.; et al. (Elsevier, 2024)
Introduction: The spectrum of clinical presentation of Fabry disease (FD) in women is broad and challenging. The aim is to evaluate the effectiveness of an alternative screening method for FD in women. Methods: A collaborative multicenter cross-sectional study to evaluate the sensitivity and specificity of the combination of two tests (α-GAL enzyme activity assay and lyso-GL3 assay) for the diagnosis of FD in women. We included women with chronic kidney disease (CKD) stages 3 to 5, receiving conservative treatment or on dialysis programs, from different nephrology services in Brazil. Results: We evaluated 1874 patients that underwent blood collection for α-GAL and lyso-GL3 assays. Isolated decreased α-GAL enzyme activity was found in 64 patients (3.5%), while isolated increased lyso-GL3 levels were found in 67 patients (3.6%), with one patient presenting alterations in both tests. All cases with low α-GAL enzyme activity and/or increased lyso-GL3 levels underwent genetic analysis for FD variants (132 performed GLA genetic test). Low α-GAL enzyme activity had higher sensitivity and specificity to detect FD compared to the other measures (elevated lyso-GL3 alone or both altered). The negative predictive value (NPV) of α-GAL activity was 99%, and the positive predictive value (PPV) was 9.2%. For lyso-GL3 assay, the specificity was 99.7% and the PPV was 2.9%, therefore considered inferior to α-GAL assay. Both assays altered, had higher PPV (100%) and higher NPV (99.7%) considered the best method. We found 7 cases of GLA gene variants found, resulting in an initial prevalence of 0.37% for FD in this sample female population. Conclusion: This study contributes to the diagnostic value of the biomarkers α-GAL and lyso-GL3 in the context of FD in women with CKD. The combination of these biomarkers was an effective approach for the diagnosis of the disease, with high PPV and NPV.
Keywords: Biomarkers; Enzyme α-galactosidase A; Fabry disease; FD diagnosis; Lyso-GL-3